THE INFLUENCE OF THE LEXICOLOGY TO THE ENGLISH AND UZBEK LANGUAGE - Turopova, Firuza (Журнал иностранных языков и лингвистики, 2023)
According to the Master’s Dissertation at the worlds Languages University of Uzbekistan which is about field of Linguistics. In this article which is about the classification of the lexicology to the Uzbek language. At first, this paper is based on information which are words, link words which is from where which is coming and etc. Secondly, the structure of the words and its own which are discussed and compared with the Uzbek language. Finally, the conclusion which is about the end of the article and its main meaning information and also given references which are used to write article.